Identification of Stem Leydig Cells Derived from Pig Testicular Interstitium - Shuai Yu; Pengfei Zhang; Wuzi Dong; Wenxian Zeng; Chuanying Pan (Stem Cells International)
Stem Leydig cells (SLCs), located in the testicular interstitial compartment in the mammalian testes, are capable of differentiating to testosterone-synthesizing Leydig cells (LCs), thus providing a new strategy for treating testosterone deficiency. However, no previous reports have identified and cultured SLCs derived from the pig. The aim of the current study was to isolate, identify, and culture SLCs from pigs. Haematoxylin and eosin staining and immunochemical analysis showed that SLCs were present and that PDGFRα was mainly expressed in the pig testicular interstitium, indicating that PDGFRα was a marker for SLCs in the neonatal pig. In addition, reverse transcription-PCR results showed that SLC markers were expressed in primary isolated LCs, indicating that they were putative SLCs. The putative SLCs were subsequently cultured with a testicular fluid of piglets (pTF) medium. Clones formed after 7 days and the cells expressed PDGFRα. However, no clones grew in the absence of pTF, but the cells expressed CYP17A1, indicating that pTF could sustain the features of porcine SLCs. To summarize, we isolated porcine SLCs and identified their basic characteristics. Taken together, these results may help lay the foundation for research in the clinical application of porcine SLCs.